pharmaceutical-sciences 2019
DOI: 10.36468/pharmaceutical-sciences.556
|View full text |Cite
|
Sign up to set email alerts
|

Antimethicillin-resistant Staphylococcus aureus and Biological Activities of Metabolites from Digitaria Sanguinalis L.

Abstract: is one of the largest vascular plant families, containing between 650 and 785 genera and 10 000 species. Poaceae is also one of the most ecologically and economically important plant families [1]. Some Poaceae plants are used in folk medicine as antihypertensive, antidiabetic, antiinflammatory, anthelmintic, astringent, antiulcer, diuretic and antioxidant agents [2]. This family is of great economic and medicinal importance as it includes all cereals, bamboos and sugar cane. Steroids, terpenoids, volatile oils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Compound 2 : Pale white powder; R f = 0.43 (90 : 10 CHCl 3 /MeOH); MP = 283 °C; it was identified as β-sitosterol 3- O -β- d -glucoside (Fig. 1) by comparing 1 H-NMR (400 MHz; DMSO- d 6 ) and 13 C-NMR (100 MHz; DMSO- d 6 ) analyses with the spectral published data, 35 see (Table S.2†).…”
Section: Resultsmentioning
confidence: 99%
“…Compound 2 : Pale white powder; R f = 0.43 (90 : 10 CHCl 3 /MeOH); MP = 283 °C; it was identified as β-sitosterol 3- O -β- d -glucoside (Fig. 1) by comparing 1 H-NMR (400 MHz; DMSO- d 6 ) and 13 C-NMR (100 MHz; DMSO- d 6 ) analyses with the spectral published data, 35 see (Table S.2†).…”
Section: Resultsmentioning
confidence: 99%
“…Also, toxic effects and antimicrobial activity studies have not been reported in the literature. However, reports exist for several plants from the Digitaria genus that possesses active phytochemicals with antimicrobial activities and other varied biological activities including analgesic, antiviral, anti-inflammatory, antitumor, anthelmintic action, and effects on the central nervous system [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, toxic efects and antimicrobial activity studies have not been reported in the literature. However, reports exist for several plants from the Digitaria genus that possesses active phytochemicals with antimicrobial activities and other varied biological activities including analgesic, antiviral, anti-infammatory, antitumor, anthelmintic action, and effects on the central nervous system [49,50]. All female Wistar rats in this study, survived after administration of a single dose of 2000 mg/kg of the aqueous, methanol, and dichloromethane : methanol (1 : 1) extracts of D. abyssinica to the Wistar rats orally.…”
Section: Discussionmentioning
confidence: 99%
“…Isoorientin ( II ) is a flavonoid glycoside found in many plants, such as Rhapis excelsa in the Arecaceae family [ 47 ], Stellaria nemorum , and Stellaria holostea in the Caryophyllaceae family [ 48 ]. Previous studies also reported various biological activities of isoorientin, such as anti-inflammatory [ 49 ], antioxidant, and antibiotic activities [ 50 ]. Isovitexin ( III ) has been isolated from some plants such as the aerial part of Lythrum salicaria [ 51 ] and the leaves of Gentiana spp.…”
Section: Discussionmentioning
confidence: 99%